Downscaling a supercritical water loop for experimental studies on system stability - Rohde, M. (2011)
In industry, supercritical water is being used as e.g. separation agent, solvent or coolant due to the unique fluid properties near the critical point. This has lead to the proposal for a nuclear reactor based on supercritical water, operating at a pressure of 25 MPa and bulk temperatures between 280 oC and 500oC. The large change of the water density in such a reactor may cause the system to become thermal-hydraulically unstable. Numerical as well as experimental investigation of this phenomenon is therefore essential. The rather high pressure, temperatures and power significantly push up the costs of an experimental facility. For this reason, we propose a scaling procedure based on Freon R-23 as the working fluid so that (i) pressure, power and temperatures are significantly reduced and (ii) the physics determining the dynamics of the system are almost completely preserved. Practical issues, such as the onset of deterioration of heat transfer, are touched upon as well.